Buffalo girls a novel - McMurtry, Larry 1936-2021 (Simon and Schuster, 1990)
Living quietly in her friend Dora's Miles City whorehouse, Calamity Jane is plunged back into one final, bittersweet adventure by the arrival of her old friend and rival, Buffalo Bill Cody.